TEACHERS’ ATTITUDES AND BELIEFS TOWARDS THE USE OF STUDENT-CENTRED LEARNING IN ENGLISH LANGUAGE CLASSES - Suriati Salleh; Nurahimah Mohd. Yusoff (Proceedings of The ICECRS, 2016)
This study was conducted to examine teachers’ attitudes and beliefs towards the use of Student-Centred Learning in English language classes. In addition, it also sought to examine the extent of student-centred learning practices amongst primary school teachers have on their students’ performance in the English language. A survey was carried out to collect data from 147 primary school English language teachers in Perlis. The questionnaires were used to determine the teachers’ beliefsand attitudes towards student-centred learning and to measure the extent teachers practice or attempt to practice student-centred learning in their classrooms. The results for March Test and mid-term examinations were also collected from 346 respondents of Year Five students to determine the relationship between student-centred learning practices and the students’ achievement. The findings of this research showed that there were positive attitudes of the English language teachers towards student-centred learning. However, the teachers employ both student-centred and teacher-centred learning strategies in teaching English language for the primary school. Apart from that, the findings also revealed that there was a positive relationship between student-centred learning practices and students’ achievement in the English language subject but the relationship was a weak relationship.As such, recommendations were proposed in terms of improving teacher training and future research to investigate further on student-centred learning practices in Malaysia.